Does the Belt and Road Initiative affect the business environment of participating countries?. Issue 3 (26th July 2022) - Chen, Yahui; Marrewijk, Charles van; Xu, Changsheng; Zuo, Congmin
Abstract: This article analyzes the impact of the Belt and Road Initiative (BRI) on the economic and business environment of its participants using the Global Doing Business Report from the World Bank. We use a difference-in-difference approach to identify the impact by considering BRI as an exogenous policy shock. We find that BRI positively impacts the business environment of the participating countries; in particular, there is a great improvement in the scores of business starting and contract enforcing. The positive effect is larger in low-income countries and the countries with a growing investment from China.